Answer:
Step-by-step explanation:
(7*5) + 42 - (23/4)
35 +42 - 5.75
71.25
Could you have meant to write the problem differently
(7*5 + 42 - 23) / 4
54 /4
13.5
Im sorry, but None of those options (with the current way its written is posible, Is the problem written exactly like that? or a way that im missing
--Gage Millar, Algebra 1/2 tutor
7.5+42−23÷4= 43.75
I hope its help you
Answer: -5
Step-by-step explanation:Absolute value is +5*-=-5
dont listen to this kid its $30.00 on APEX
-6= - 9 - 3x
3x = -9 + 6
3x = - 3
Therefore x = -1